KECERDASAN VERBAL-LINGUISTIK ANAK MELALUI PENDEKATAN BEYOND CENTERS AND CIRCLE TIME (BCCT) - Farhatin Masrurah (LP2M Universitas Ibrahimy, 2014)
Language is a communication to obtain and convey information and science by oral and written. Verbal linguistic intelligence of children implemented in an integratedÂ with other activities while learning and playing. BCCT approach that emphasizes the play activities as core activities and child-centered (student centered) is a good method for the child to actualize linguistic verbal intelligence. BCCT approach is method relevanted to the principle of development and early childhood characteristics that are unique. TK ABA Nur'aini is the only elementary school in DI Yogyakarta that implementing a purely CCCRT (The Creative Center for Childhood Research and Training) Florida and Department of Education